1998
DOI: 10.1046/j.1365-2362.1998.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plasma phytanic acid levels in Refsum's disease on the behaviour of the erythrocyte membrane sodium–lithium countertransporter

Abstract: These findings suggest that phytanic acid may alter the behaviour of the sodium-lithium countertransporter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It has also been shown that SLC activity can be affected by the identity of fatty acids with a reduction in activity with the alpha-methylated fatty acids in Refsum's disease. 17 Membrane function has been shown to be affected by these fatty acids 18 and also by cholesterol. 10 The aims of this study were to investigate whether SLC kinetics were affected by severe hypercholesterolaemia in the absence of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that SLC activity can be affected by the identity of fatty acids with a reduction in activity with the alpha-methylated fatty acids in Refsum's disease. 17 Membrane function has been shown to be affected by these fatty acids 18 and also by cholesterol. 10 The aims of this study were to investigate whether SLC kinetics were affected by severe hypercholesterolaemia in the absence of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…the physical state of cellular membranes may change [Young et al, 2001;Schönfeld and Struy, 1999;Wierzbicki et al, 1998;Gutknecht, 1987;Janko and Benz, 1977], which could interfere with proper membrane function. So far, direct evidence for the role of this ''membrane distortion'' in the development of clinical symptoms in RD has not been provided.…”
Section: Pathogenesismentioning
confidence: 99%